Organizational Support, Work Commitment, And Job Performance: Motivation As A Moderating Variable - Azis Do Ali (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to examine the causal relationship between organizational support, work commitment, and personnel performance, and assess the role of motivation as a moderation variable in strengthening the influence of work commitment on performance. The study used a quantitative approach with an explanatory type and was carried out at the Directorate of Special Criminal Investigation (Ditreskrimsus) of the Southeast Sulawesi Police with 130 active respondents. Data collection was carried out through a closed questionnaire arranged based on the indicators of each variable, then measured using a five-point Likert scale from strongly disagree to strongly agree. The sampling technique uses purposive sampling with the criteria that personnel have a minimum working period of two years and are directly involved in operational tasks. Data analysis was carried out using Structural Equation Modeling based on Partial Least Squares with the help of SmartPLS, through the outer model evaluation stage to test validity and reliability as well as internal model evaluation to test structural relationships and moderation effects. The results of the study show that motivation does not have a significant effect directly on personnel performance. However, organizational support has a positive and significant effect on performance, and has a very strong effect on work commitment. Work commitment has also been proven to have a positive and significant effect on personnel performance. In addition, motivation has been shown to significantly moderate the relationship between work commitment and performance, so that the influence of commitment on performance becomes stronger when personnel motivation is high. These findings affirm the importance of strengthening organizational support to build work commitments, as well as motivation enhancement strategies so that the commitments formed can be optimally actualized in improving personnel performance.